A study of two highly conserved baculovirus genes - Lehiy, Christopher J. (Kansas State University, 2012)
Baculoviruses are enveloped, rod shaped viruses with circular, double-stranded DNA genomes. These viruses infect arthropods, primarily in the order Lepidoptera, although members of this virus family also infect species of Diptera, Hymenoptera, and Crustacea. The majority of these viruses undergo a bi-phasic cycle with one phase defined by the production of a budded virus (BV) form, responsible for cell to cell transmission, and the other defined by the production of an occlusion-derived virus (ODV) form, responsible for host to host transmission. The proto-typical member of the Baculoviridae family is considered to be Autographa californicaM Nucleopolyhedrovirus (AcMNPV). Its 133,894 base pair genome is predicted to encode for 156 proteins, a large number of which are essential for virus replication.. In this current work, we have further characterized two viral proteins that are highly conserved among baculoviruses. The first of these is an ortholog of the fibroblast growth factor family of proteins with sequence homology to the Drosophila Branchless protein as well as the mammalian FGF- 9, -16 and -20 subfamily. Despite its high degree of conservation among baculoviruses, the viral fibroblast growth factor (vFGF) is considered a non-essential protein, although its deletion from the genome does affect the lethality of the virus when ingested per os. In our study, we were able to localize vFGF to the membrane of BV. Its presence on the envelope affected the ability of the virus particle to bind to both heparin in vitro and to the cell surface in vivo, and may play a role in the attachment phase prior to virus entry. We also characterized AcMNPV’s open reading frame 109 (Ac-orf109). Unlike vFGF, Ac-orf109 is essential for virus replication since its deletion results in a complete lack of BV production. Transmission electron microscopy of cells transfected with an Ac-orf109 deletion virus shows the full range of virus-associated structures including mature capsid formation but there appears to be a deficiency in capsid egress out of the nucleus. Furthermore, the ODV retained in the nucleus appear to lack microvesicular membranes, an essential component for host to host transmission of infection.
Keywords: Baculovirus; vFGF; Ac-orf109; Virology (0720)